Evaluation of Microorganism Colonization on Laparoscopic Instruments after Surgery and Following Two Different Cleaning Methods - Sorour Mosleh; Hossein Fazeli; Hassan Farahmand; Akram Aarabi (مجله دانشکده پزشکی اصفهان, 2018)
Background: An accurate cleaning, as the first step of reprocessing, would make the sterilization more effective, and protects healthcare providers and patients against infections. The present study aimed to compare the effect of two cleaning methods of conventional and the Association for the Advancement of Medical Instrumentation (AAMI) on the reduction of microorganism colonization on laparoscopic instruments.